The twelve-mile straight [compact disc, unabridged] - Henderson, Eleanor (Harper Audio, 2017)
Cotton County, Georgia, 1930: in a house full of secrets, two babies, one light-skinned, the other dark, are born to Elma Jesup, a white sharecropper's daughter. Accused of her rape, field hand Genus Jackson is lynched and dragged behind a truck down the road to the nearby town. In the aftermath, the farm's inhabitants are forced to contend with their complicity in a series of events that left a man dead and a family irrevocably fractured. Despite the prying eyes and curious whispers of the townspeople, Elma begins to raise her babies as best as she can, under the roof of her mercurial father, Juke, and with the help of Nan, the young black housekeeper who is as close to Elma as a sister. But soon it becomes clear that the ties that bind all of them together are more intricate than any could have ever imagined.